2012
DOI: 10.1111/j.1470-6431.2011.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of socio‐demographical, behavioural and attitudinal factors on the amount of avoidable food waste generated in Finnish households

Abstract: This paper presents the results of a questionnaire and food waste diary study on the influence of socio‐demographical, behavioural and attitudinal factors on the amount of avoidable household food waste in 380 Finnish households. The research data were collected through a 2‐week food waste diary study accompanied by a background questionnaire. The influences of socio‐demographical, behavioural and attitudinal factors on the production of food waste were studied through application of descriptive statistics. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
345
8
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 396 publications
(434 citation statements)
references
References 8 publications
36
345
8
12
Order By: Relevance
“…Furthermore, Lily Zakiah et al (2005) found from their food wastes composition study, vegetable was the most wasted food items, while the females wasted significantly higher than males for all meals. This finding is similar to that of Koivupuro et al (2012) that single women generate more avoidable food wastes than their male counterparts. The reasons found contributing to plate waste at home ranges from food size, appetite, appearance of food, and temperature of foods and the time foods was served were factors found significantly contributing to food waste.…”
Section: Food Wastes In Malaysiasupporting
confidence: 86%
“…Furthermore, Lily Zakiah et al (2005) found from their food wastes composition study, vegetable was the most wasted food items, while the females wasted significantly higher than males for all meals. This finding is similar to that of Koivupuro et al (2012) that single women generate more avoidable food wastes than their male counterparts. The reasons found contributing to plate waste at home ranges from food size, appetite, appearance of food, and temperature of foods and the time foods was served were factors found significantly contributing to food waste.…”
Section: Food Wastes In Malaysiasupporting
confidence: 86%
“…Consumers' food waste behaviors are directly related to planning and shopping routines [50], having or lacking an overview of stocks, having or lacking knowledge about whether food can still be used and situational influences (e.g., specific purchase or consumption contexts; [51]). A diary study in Finland identified that gender, household composition, belief in packaging and perception of the "value of money" at purchase influence food waste [52], while it was mainly young, male and single consumers in research in Portugal [53] that wasted more food.…”
Section: Consumer Behavior Research Regarding Food Wastementioning
confidence: 99%
“…Some distinctive characteristics of the urban households show significant correlations with the amount of FW individually produced. Households consisting of few members or one single person, of young members, of children, and relatively high income seem to be the features that are mostly related with higher FW production per capita [9,[13][14][15][16]22,30,55,104,[146][147][148][149][150][151]. Direct comparisons between urban and rural households indicate that the former are significantly higher FW producers [15,152].…”
Section: Fw Drivers Related To Wide Social Dynamics That Are Not Readmentioning
confidence: 99%
“…According to several surveys, consumers in general deem that modern "busy" lifestyles make it much more difficult to perform good practices correctly that facilitate FW avoidance [16,25,[153][154][155][156]: in this sense, sociological analyses defined FW as "the fallout of the organization of everyday life" [136], and "a consequence of households enacting ordinary domestic practices and negotiating the contingencies of everyday life" [157]. Authors have also found gender-based diversities in FW generating behaviours, with women that seem to waste more than men in households [14,30,55,153,158,159], especially in single-person households and in meal consumption out of home because of excessive portion size [23].…”
Section: Fw Drivers Related To Wide Social Dynamics That Are Not Readmentioning
confidence: 99%